Causal Linkage between Political, Economic, Institutional Governance & Economic Growth: An evidence from the selected GCC Countries (Journal of Governance and Development (JGD), 2019)
The current study measures the causal relationship between governance and economic growth in GCC countries from 2001 until 2016 with Granger causality. This study found the economic governance and institutional governance are signiï¬cant to the GCC economic development, while the political governance is not signiï¬cant. There is bidirectional causality between institutional governance and growth. Evidence of bidirectional causality between economic governance and growth in GCC countries also implied the liberalisation of the market matters for their economic development. In other words, although political governance does not cause economic growth, the ï¬nding of unidirectional causality from institutional governance and political governance suggest that the political leaders might inï¬‚uence the democracy of the GCC countries. A major policy implication emanating from the ï¬ndings was that the economic governance and the institutionâ€™s governance were crucial to the achievement of sustained economic growth in GCC countries due to the reinforcing effect. However, both economic governance and institution governance are independent of each other.